KODE SASTRA, KODE BAHASA, DAN KODE BUDAYA DALAM CERITA PENDEK “SENYUM KARYAMIN” KARYA AHMAD TOHARI - Fatimatu Seha, Ghina Nasuha (Hasta Wiyata, 2023)
This article presents the results of research on allusions in a short story entitled “Senyum Karyamin” by Ahmad Tohari. This research analyzes language code, literary code, and cultural code. The approach taken is a textual approach which emphasizes its analysis on the linguistic side of understanding texts. The data source is from Ahmad Tohari’s short story, “Senyum Karyamin”. The results of the analysis of the short story "Senyum Karyamin" found literary codes such as theme, plot, characters, setting, point of view and moral value. The results of the analysis of the language code in "Senyum Karyamin" by Ahmad Tohari found figures of speech, conversion and absorption. The Cultural Code depicted in short story Senyum Karyamin contains a social system and cultural values.